METODOLOGI PEMIKIRAN HUKUM SyI’AH IMAMIyAH DAN PENERAPANNyA DALAM FIQH (kajian Terhadap Kitab al-Mabsuth Fi Fiqh Imamiyah karya al-Thusi) - Busyro, Busyro (Alhurriyah, 2012)
Syiah Imamiyah school of the thought and it`s relation with Islamic law has given birth to some conclusion about law which are often different from the conclusion about law expressed by shool of thought of the Jumhur. These differences are caused by the different method each school of thought is using. AlThusi is one of the leading actor of mujtahid Syi’ah Imamiyah who was very famous and his ideas has been referred to by most af the Syi’ah. His thought in fiqh mostly followed the method of istinbath law which is agreed upon all the Syi’ah. AlThusi`s concept of understanding of the verses in Quran, the different terminology of Sunnah and Ijma’, Qiyas and Qaul alShahaby that he refused and some Istishab that he commonly used draw a conclusion about law which is different from the Jumhur. The balance between the ijtihad method in his shool of thought and the idea about fiqh that he expressed are generally found in the research about his monumental work, kitab alMabsuth Fi Fiqh Imamiyah.